Proceedings of the 8th ACM Conference on Recommender Systems 2014
DOI: 10.1145/2645710.2645729
|View full text |Cite
|
Sign up to set email alerts
|

LinkedIn skills

Abstract: Skills and Expertise" is a data-driven feature on LinkedIn, the world's largest professional online social network, which allows members to tag themselves with topics representing their areas of expertise. In this work, we present our experiences developing this large-scale topic extraction pipeline, which includes constructing a folksonomy of skills and expertise and implementing an inference and recommender system for skills. We also discuss a consequent set of applications, such as Endorsements, which allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The feasibility of large-scale studies of SM users has been demonstrated for a variety of text-based SM platforms, such as LinkedIn (Bastian et al, 2014), Facebook (Heidenreich et al, 2020) or Twitter (Giachanou & Crestani, 2016). Widespread methods for the analysis of such data include topic modelling (Calderón et al, 2020) and sentiment analysis (Giachanou & Crestani, 2016).…”
Section: Background: Analysis Of Migrants Using Smmentioning
confidence: 99%
“…The feasibility of large-scale studies of SM users has been demonstrated for a variety of text-based SM platforms, such as LinkedIn (Bastian et al, 2014), Facebook (Heidenreich et al, 2020) or Twitter (Giachanou & Crestani, 2016). Widespread methods for the analysis of such data include topic modelling (Calderón et al, 2020) and sentiment analysis (Giachanou & Crestani, 2016).…”
Section: Background: Analysis Of Migrants Using Smmentioning
confidence: 99%
“…Past editions of the RecSys conference have seen a steady number of research contributions on automating and (more commonly) supporting job recommendation [3,7,9,11,13,17,19], all of which have focused on the core HR task of recruitment through the development of automatic job recommendation algorithms. In addition to this research, the RecSys Challenges of 2016 [1] and 2017 [2] both focused on the task of job recommendation, with Xing, a social network for businesses mainly operating in German-speaking countries, providing the training data.…”
Section: Relevance For Recsysmentioning
confidence: 99%
“…The LinkedIn Skills system (Bastian et al 2014) uses a data-driven approach to build a skills folksonomy. The folksonomy-building pipeline consists of discovery, disambiguation, and deduplication steps.…”
Section: Large-scale Occupational Skills Normalization For Online Rec...mentioning
confidence: 99%